Longitudinal relations between psychological distress and moderate-to-vigorous physical activity: A latent change score approach. (March 2020) - Gucciardi, Daniel F.; Law, Kwok Hong; Guerrero, Michelle D.; Quested, Eleanor; Thøgersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Jackson, Ben
Abstract: Objectives: The effect of physical inactivity on mental health risk is well established; however, less is known about about how psychological distress might deter participation in physical activity. Guided by advancements in the treatment of longitudinal data, the aim of this study was to examine patterns and predictors of change in moderate-to-vigorous physical activity (MVPA) and psychological distress (e.g., feeling nervous, worthless). Design method: Australian adults (4944 females, Mage = 34.63 years ±5.34; 4322 males, Mage = 37.51 years ±6.14) provided baseline data as part of the Longitudinal Study of Australian Children (LSAC) and were followed for measurements every two years for 10 years. Results: Latent change score analyses revealed support for a reciprocal effects model, whereby change in MVPA and psychological distress occurred as a function of individuals' prior levels of, and/or prior change in these variables. Conclusions: This investigation is the first to document that changes in MVPA and psychological distress are coupled temporally. Notably, we observed that individuals' distress levels at a given time point predicted subsequent change on both MVPA and distress; a finding which provides novel and important insight into how adults' activity levels and psychological distress fluctuate relative to one another. Highlights: Self-reports of MVPA decreased over time, whereas psychological distress increased throughout the 10-year period. Psychological distress and MVPA at previous measurement wave were associated positively with distress at subsequent waves. Upward changes in psychological distress downregulated future moderate-to-vigorous physical activity. Higher levels of distress reported the previous wave were associated with greater decreases in MVPA at the subsequent wave.